Evolution of Global Cooperation in Multi-Level Threshold Public Goods Games With Income Redistribution - Du, Jinming; Wang, Baokui (Frontiers in Physics, 2018)
Income redistribution is a feasible means to adjust the income among individuals, which could reduce the gap between the rich and the poor and realize the social equity. By means of taxation and public services, the income could be transferred from some individuals to others directly or indirectly. We study how income redistribution affects the evolution of global cooperation through proposing a multi-level threshold public goods game model and introducing two kinds of income redistribution mechanisms. We find that both of the income redistribution mechanisms promote global cooperation. Furthermore, the global income redistribution is more in favor of the emergence of global cooperative behaviors than the local income redistribution mechanism. On the other hand, the fixation time of global cooperation is sharply shortened after introducing income redistribution mechanisms. In threshold public goods games, only when the amount of collected public goods reaches a certain threshold, the income of individuals can be guaranteed. Hence, the influences of thresholds of different levels on strategies are investigated in the paper.